Studies Of Ionic Conductivity And A.C. Conduction Mechanism Of 2-Hydroxyethyl Cellulose Based Solid Polymer Electrolytes - Nur Hafiza Mr Muhamaruesa; Mohd Ikmar Nizam Mohamad Isa (Penerbit UMT, 2024)
Indexed by SCOPUS